Från skolans medborgarbildande möjlighet till samhällskunskapsämnets – en väg framåt? - Maria Olson (Utbildning & Demokrati)
What is good citizenship, and how can schools help to promote and shape it? This text seeks to define a possible path for citizenship-oriented social studies education that is able to respond to this question in a satisfactory way. To that end, I pursue two different lines of inquiry. On the one hand, I proceed from an idea of citizenship drawn from established political theory with a focus on citizenship, specifically the work of Joel Westheimer and Joseph Kahne (2004). On the other, I undertake a far from complete, but nevertheless pertinent, review of research into the subject didactics of social studies – the what, how and why of teaching and learning the subject – in the light of the question of what invitations to citizenship can be traced in that research. Based on these two lines of inquiry, four subject-specific dimensions are distinguished that seem to be necessary points of reference for social studies as a school subject if the aim is to promote citizenship education: a social, a knowledge-related, a personal and an explicitly normative dimension.